Antibacterial efficacy of manuka honey, ocimum sanctum, curcuma longa and 0.2% chlorhexidine mouthwash on the level of streptococcus mutans and lactobacillus acidophilus - A randomized controlled trial - Ankita Jain; Vikas Singh; Anooj Lukram; Silpi Chatterjee; Asim Mustafa Khan; Geetanshu Dawar (Wolters Kluwer Medknow Publications, 2022)
Objective: To assess the effects of Manuka honey, Ocimum sanctum, Curcuma longa, and 0.2% chlorhexidine mouthwash on Streptococcus mutans and Lactobacillus acidophilus levels. Material and Methods: A randomized controlled trial will be conducted on dental students of Teerthanker Mahaveer Dental College and Research Centre, Moradabad. The study participants will be divided into four groups. Each group will have a total of 20 individuals. By using a lottery system, Group A (Manuka honey mouthrinse), Group B (Ocimum sanctum mouthrinse), Group C (Curcuma longa mouthrinse), and Group D (0.2% chlorhexidine mouthrinse) will be chosen. To match the circadian cycle, saliva will be collected at baseline and again after 2 weeks between 10 and 10.30 a.m. The sterile container will subsequently be delivered to the microbiological laboratory and processed as soon as possible to measure Streptococcus mutans and Lactobacillus acidophilus count. For 2 weeks, participants were told to use 10 mL of mouthrinse twice daily. Results: The mean oral hygiene index-simplified (OHI-S) score of all the four groups showed reduction in their scores from baseline to after the study period. For both S. mutans and L. acidophilus, there was a substantial Percentage Reduction (PR) between the prerinse and postrinse samples in all four groups. Discussion: Because quantitative actions play a crucial part in the caries disease process, the changes in microbial activity before and after administration of experimental mouthwashes were examined. Conclusion: Essential oil aqueous extracts were as efficient antibacterial mouthwashes as chlorhexidine and iodine mouthwashes.